Rebel rule: A governmentality perspective. Issue 471 (19th September 2018) - Hoffmann, Kasper; Verweijen, Judith
Abstract: Much of the recent literature on rebel governance and violent political orders works with 'centred' and instrumental understandings of power. In this view, power is seen as exercised over subjects, and as situated in rebel rulers, governance institutions, or ruling networks. Drawing on the study of the armed groups known as 'Mai-Mai' in eastern Democratic Republic of the Congo, this article instead adopts a governmentality perspective on rebel governance. It demonstrates how Mai-Mai groups rule not only through direct imposition but also, more subtly, by shaping people's subjectivities and self-conduct. We identify four clusters of techniques of Mai-Mai rule that relate respectively to ethnicity and custom; spirituality; 'stateness'; and patronage and protection. We argue that a governmentality perspective, with its focus on rationalities and practices of power, offers a fine-grained understanding of rebel rule that moves beyond common binaries such as coercion versus freedom. By showing its relevance for the analysis of rebel rule in the eastern Congo, our findings further strengthen the case for applying a governmentality perspective to non-Western political orders.